COST ASPECTS OF COMPLIANCE IN REGARD TO THE VALUE ADD OF APPLIED MEASURES TO ENHANCE ETHICAL BUSINESS CONDUCT - Gammisch, Malcolm (European Scientific Journal, ESJ, 2015)
Compliance management systems provide assurance for a company and help to stir the business in accordance with internal and external rules and regulations. This paper elaborates on the cost aspect of compliance. Compliance measures cost money and it is asked by business executives if the money spent on compliance is wisely spent. Starting from a conceptual approach and based on a laboratory experiment concrete suggestions for meaningful activities are made.